Population structure of the broad-snouted caiman (Caiman latirostris) in natural and man-made water bodies associated with a silvicultural landscape - Marques, Thiago Simon; Bassetti, Luis Antonio Bochetti; Lara, Neliton Ricardo Freitas; Millan, Cristiane Honora [UNESP]; Piña, Carlos Ignacio; Verdade, Luciano Martins (My University, 2016)
The broad-snouted caiman (Caiman latirostris) is a South American crocodilian with a wide geographical distribution. Water bodies originally occupied by the species have suffered extreme anthropogenic pressure; however, the broad-snouted caiman has a high adaptive capacity to colonize man-made habitats such as decanting pounds and artificial reservoirs for agriculture or livestock. In this context, the present study aimed at identifying the population structure of the broad-snouted caiman in a silvicultural landscape in southeastern Brazil. Fifty-two caimans of various classes were captured with baited traps and steel cable snares at night. The estimated population size was 51 individuals excluding class I individuals. The population density was estimated to be 2.6 individuals/ha with a linear density of 11.3 individuals/km. The intermediate values of linear density estimates herein are similar to other areas, suggesting that silvicultural landscapes can be relevant for broad-snouted caiman conservation. Therefore, the role of silvicultural landscapes in crocodilian conservation should be taken into consideration for environmental certification processes related to forestry in the Neotropics.
Keywords: Anthropogenic environments; Biomass; Conservation; Crocodilians; Distribution; Forestry plantations; Linear density; Population density; Sex ratio; Sexual dimorphism